A large catalog of young active RAVE stars in the Solar neighborhood. Issue Volume 12:Issue S328(2016) (12th September 2017) - Žerjal, Maruša; Zwitter, Tomaž; Matijevič, Gal; ,
Abstract: The catalog of 38, 000 chromospherically active RAVE dwarfs represents one of the largest samples of young active solar-like and later-type single field stars in the Solar neighbourhood. It was established from the unbiased magnitude limited RAVE Survey using an unsupervised stellar classification algorithm based merely on stellar fluxes (Ca II infrared triplet). Using a newly-calibrated age-activity relation, 15, 000 active stars are estimated to be younger than 1 Gyr. Almost 2000 stars are presumably younger than 100 Myr and possibly still in the pre-main sequence phase, the latter being supported by their significant offset from the main sequence in the N UV − V versus J − K space. 16, 000 stars from the sample have positional and velocity vectors available (using TGAS parallaxes and proper motions and radial velocities from RAVE).